Financial inclusion of the poor and money laundering indicators: empirical evidence for Colombia (2017)
Taking advantage of the largest financial inclusion program in Colombia, we estimate how increasing the access to such services for the poor impacts money laundering indicators in the country. We find that eventhough, on average, government's indicators of money laundering activities in Colombia decreased, complex and heterogeneous impacts across the country and in time are observed. While money laundering indicators decreased in areas with high historic values of this crime, indicators in areas with medium historic levels increased. The evidence suggests that after the banalization process a fragmentation and expansion of money laundering indicators across municipalities in Colombia took place, diminishing the accuracy of the alerts that the financial institutions provide to the government in order to fight this crime.